Pre-harvest Application of Putrescine Influences Japanese Plum Fruit Ripening and Quality - Khan, Ahmad; Singh, Zora (Sage Publications, 2010)
To investigate the role of pre-harvest application of putrescine (PUT) in regulating fruit ripening and quality of early-, mid- and late-season maturing Japanese plum fruit, whole trees were sprayed with an aqueous solution containing PUT (0, 0.1, 1.0 and 2.0 mM) one week before anticipated commercial harvest for each cultivar separately. The PUT (2.0 mM) treatment reduced the respiration rate and ethylene production more than untreated fruit during fruit ripening at ambient temperature (20±1 °C). Activities of ACS and ACO enzymes, and ACC content were delayed and suppressed in all plum cultivars and these effects were more pronounced with higher PUT concentrations. PUT application reduced the fruit softening, soluble solids content, titratable acidity ratio, the levels of ascorbic acid, total carotenoids and total antioxidants in all plum cultivars. ‘Black Amber’ did not exhibit any change in fruit color parameters, while, PUT application to ‘Amber Jewel’ and ‘Angelino’ fruit, delayed the changes in chroma value and hue angle during fruit ripening. In conclusion, pre-harvest application of 2.0 mM PUT delayed the fruit ripening with reduced respiration rate, ethylene production, activities of ACS and ACO enzymes, ACC content, fruit softening, levels of ascorbic acid, total carotenoids and total antioxidants in Japanese plum.